161 The association of non-invasive cardiovascular parameters on adverse outcomes in older patients following non-ST elevation acute coronary syndrome undergoing invasive care. (May 2019) - Chan, Danny; Beska, Ben; Gu, Sophie; Neely, Dermot; Kunadian, Vijay
Abstract : Introduction: Ischaemic heart disease (IHD) leads to poor outcomes in those aged ≥75 years. Non-invasive assessment of cardiovascular status is associated with adverse events in younger patients but this has not been evaluated in older patients. The aim of the study is to investigate whether non-invasive assessments of cardiovascular status could be used as predictors of poor outcomes in older patients with non-ST-elevation acute coronary syndrome (NSTEACS) undergoing invasive care. METHOD: Older patients undergoing invasive management for NSTEACS were recruited. Cardiovascular status was assessed through evaluation of carotid intima media thickness (CIMT) via B-mode ultrasound (Vivid-I, GE Healthcare), vascular stiffness was assessed through carotid-femoral pulse wave velocity (PWV) (Vicorder device, Skidmore Medical Limited, Bristol, UK), and peripheral arterial endothelial function (EndoPAT 2000 device; Itamar Medical, Caesarea, Israel). Primary outcome consisted of composite of death, myocardial infarction (MI), unplanned revascularisation, stroke and significant bleeding at 1 year. Results: Of the 629 patients screened, 300 patients were recruited into the study. 2 patients had other diagnosis post angiography and were excluded, and a further 1 patient lost to follow-up, meaning sample available for analysis was 297. Overall, 276 (93%) had non-invasive cardiovascular status assessed at baseline of which 219 (74%) had CIMT, 276 (93%) had vascular stiffness and 242 (88%) had endothelial function data available for analysis. Mean age was 80.5 ± 4.8 years and 60.5% were male. The primary outcome at 1 year was observed in 75 patients (27.2%). Cumulative event rates for primary end points were significantly higher in patients with CIMT ≥0.9mm when compared with <0.9mm (48.4% vs. 22.9% Hazard Ratio [HR] 2.39, 95% Confidence Interval [CI]: 1.33–4.31, P<0.05) driven mainly by bleeding events (Odds Ratio [OR] 5.15, CI: 1.80–14.78, P<0.01). Patients with an abnormal CIMT were 3 times more likely to meet the primary end-point (Odds Ratio OR 3.16, 95% CI: 1.45–6.91, P<0.01), with the association remaining after adjusting for age, gender, frailty and previous MI (OR 3.15, 95% CI: 1.41–7.07, P<0.01). Increased vascular stiffness (PWV >10m/s) was associated with a significant reduction in mortality after adjusting for age, gender, frailty and previous MI (OR 0.12, 95% CI: 0.014–0.98, P<0.05). Endothelial dysfunction as hyperaemia index <0.40 vs. ≥0.40 showed no significant differences in the event rates of combined primary end points adjusting for age, gender, frailty and previous MI (27.3% vs. 25.0%, HR 0.91, 95% CI: 0.49–1.70, P=0.71). Conclusion: Increased CIMT is associated with adverse outcomes driven by excess bleeding events. Vascular stiffness is associated with reduced mortality in older patients with NSTEACS, even after traditional risk factors for cardiovascular events have been taken into consideration. Endothelial dysfunction is not associated with adverse events. Figure 1. Conflict of Interest: None